(untitled) (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 2015)
Many orthopaedic operations involve drilling before the insertion of implants into the bones. Usually drilling is executed manually, which may cause some problems. In free hand performance of drilling some errors such as an inaccurate penetration and dilate of bone hole, overheating, harm soft tissues could be occurring. Automatic drilling is recommended to avoid such problems and reduce the subjective factor. The aim of this paper is to select, develop and test a new sensor system for a bone drilling robotized system. More in particular we utilize a sensor to measure thrust force during the bone drilling manipulation execution. Therefore a force sensor is fixed to the drilling robotized system. Moreover, an experimental identification of the drilling technical parameters such as bone resistant force and feed rates are done. The resistant forces are measured and plotted. The control algorithms and programs for drilling have done based on the experiments.